Los derechos sociales y el camino hacia su efectivo reconocimiento - Martínez, José Mateos (2023)
Social rights create legal conditions that are necessary so that a person‘s dignity is safeguarded and everyone is allowed to exercise his or her freedoms and to develop his or her personality. In spite of this, social rights had not been recognized by law until relatively recent times, and, even after being legally recognized, they were ineffective becaus e there were no legal actions that allowed a person to demand their enforcement. In this essay, we will consider the importance of social rights and their historical evolution. We will also analyze the most suitable and recent techniques of protection that have been created in different jurisdictions in order to guarantee the respect of these rights, whose absence annuls in practice the efficacy of the entire set of fundamental rights.